The forgotten man ebook - Crais, Robert (Elvis Cole and Joe Pike, 2005)
“[A] riveting novel with a vivid sense of place . . . Anyone who enjoys a well-written, fast-paced, noirish thriller with a great aha! moment shouldn’t miss The Forgotten Man .”— The Boston Globe In an alleyway in Los Angeles, an old man, clutching faded newspaper clippings and gasping his last words to a cop, lies dying of a gunshot wound. The victim claims to be P.I. Elvis Cole’s long-lost father—a stranger who has always haunted his son. As a teenager, Cole searched desperately for his father. As a man, he faces the frightening possibility that this murder victim was himself a killer. Caught in limbo between a broken love affair and way too much publicity over his last case, Cole at first resists getting involved with this new case. Then it consumes him. Now a stranger’s terrifying secrets—and a hunt for his killer—give Cole a frightening glimpse into his own past. And he can’t tell if it’s forgiveness or a bullet that’s coming next. . . .  “Robert Crais is a crime writer of incredible talent—his novels are not only suspenseful and deeply atmospheric but very hard to put down.”—Dan Brown, author of The Da Vinci Code “A brutal but exhilarating climax.”— USA Today